Service life of building elements: An empirical investigation - Benjamin Volland; Mehdi Farsi; Sébastien Lasvaux; Pierryves Padey (University of Neuchâtel, Institute of Economic Research (IRENE), 2020)
Improvements in building's energy-efficiency hold considerable potential for decreasing energy consumption. Yet, renovations in the building stock could occur belatedly and without the coordination required for fully tapping the energy reduction potentials. In this paper, we use data from a household survey in Switzerland to analyse replacement patterns for windows, heating systems, façades and roofs. As opposed to most previous studies that assume a linear age effect, we model the renovation probability as a conditional hazard rate with a more flexible representation of age effects. We compare the renovation patterns identified by the survival analysis with the service lives determined by building norms. We find systematic deviations between the two, suggesting sub-optimal replacement in many cases, especially for the building envelope. In particular, the results point to a considerable fraction of cases, where the owners refrain from renovation far beyond the end of an element's technical service life. Moreover, the strong differences in renovation timing across various elements could hinder the expected energy savings. We identify a number of determinants for replacement timing, in view of energy policies aiming at the promotion of energy-saving renovations in buildings.
Keywords: D10; Q40; Q48; 330; Renovation patterns; Survival analysis; Hazard models; Switzerland